Nanometer solid cerium dioxide with bowl-shaped morphology and preparation method thereof

The preparation of nano-solid ceria with bowl-shaped morphology by solvent-thermal method was solved, and the problems of poor dimensional uniformity, insufficient activity and high preparation cost in the CMP process were solved, achieving efficient polishing and cost reduction effects.

CN119503857APending Publication Date: 2025-02-25FUDAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411967988.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the CMP process, existing CeO2 nanoparticles have problems such as poor dimensional uniformity, insufficient particle activity and catalytic capacity, unsatisfactory surface morphology control and high preparation cost.

Method used

Nano-solid ceria with bowl-shaped morphology was prepared by solvothermal method. By adjusting the reaction conditions and the amount of deionized water, the particle size and morphology of the particles were controlled to improve their activity and catalytic ability.

Benefits of technology

The prepared CeO2 nanoparticles have high activity and catalytic capabilities, which improve the polishing effect, reduce the risk of scratches, stabilize the polishing rate, and reduce the cost of the CMP process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503857A_ABST
    Figure CN119503857A_ABST
Patent Text Reader

Abstract

The invention relates to nano solid cerium dioxide with large-opening bowl-shaped morphology and a preparation method thereof, in particular to bowl-shaped solid cerium dioxide nano powder with high specific surface area and uniform particle size prepared by a solvothermal method, which can meet the requirement of a new preparation technology on the surface flatness of a semiconductor. And the overall performance and efficiency of the CMP process are improved. The preparation method is simple and has low requirements on equipment; the raw materials are low in price, no surfactant needs to be added, repeatability is good, and the CMP process cost can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nano powder technology, and in particular to a nano solid cerium dioxide with a bowl-shaped morphology and a preparation method thereof. Background Art

[0002] As semiconductor process nodes continue to shrink, the requirements for semiconductor surface flatness are also increasing. Chemical mechanical polishing (CMP) is currently the key process to achieve global flatness of integrated circuits. CMP uses the synergistic effect of chemical reaction and mechanical action to react between the polishing liquid and the thin film on the wafer surface to generate a softer layer, which is then polished away under the mechanical action of the polishing pad and abrasive particles. The most core consumable in the CMP process is the polishing liquid, which accounts for about 50% of the cost, and the demand is still growing rapidly.

[0003] The abrasives in the polishing liquid are mainly inorganic oxide nanoparticles, including cerium oxide (CeO2), silicon oxide (SiO2), aluminum oxide (Al2O3), manganese oxide (MnO2), zirconium oxide (ZrO2) and diamond, which can perform mechanical friction, adsorb and remove corrosion products. Al2O3 abrasives are hard (Mohs hardness 9) and have good resistance, but they are easy to agglomerate, the polishing liquid has high viscosity and is difficult to clean. They are widely used in CMP of hard materials such as sapphire, alloy, silicon carbide, and optical glass. SiO2 abrasives are simple to synthesize, have excellent dispersibility and stability, and are inexpensive, but have low hardness (Mohs hardness 7) and low polishing rate. They are often used for polishing zirconium oxide ceramics, sapphire, and dielectric layers. However, with the miniaturization and precision of semiconductor devices, higher requirements for CMP polishing performance are required, such as high selectivity with high removal rate and low scratch defects, and polishing liquids with self-stop function.

[0004] CeO2 has a good crystal structure and excellent tribochemical activity, and has a strong affinity for SiO2. It can use surface chemical reaction softening and particle embedding cutting to achieve efficient removal of silicon oxide. CeO2 is also a semiconductor photocatalyst with variable valence states (Ce 4+ and Ce 3+ ) and can form oxygen vacancies, Ce 3+ The presence of ions makes cerium dioxide have strong redox ability and can enhance the adsorption and activation ability of the catalyst to the reactants; oxygen vacancies can reduce the band gap of the material, extending its light absorption boundary to the visible light and even the near-infrared band, thereby enhancing the photocatalytic activity of the material. CeO2 combines tribochemical ability and photochemical oxidation activity and can be used for photocatalytic assisted polishing. In view of this, CeO2 has become the preferred polishing material for oxides such as interlayer dielectric SiO2 and has received extensive attention and research.

[0005] At present, CeO2 has the following shortcomings when used as an abrasive in the CMP process: (1) Due to the preparation process, the uniformity of CeO2 particle size is poor and the particle concentration is difficult to control, resulting in unstable polishing rate. (2) The trivalent cerium and oxygen vacancies contained in CeO2 particles are insufficient, making it difficult to achieve higher particle activity and catalytic ability. (3) Fine control of the surface morphology of CeO2 particles, such as forming a bowl-shaped structure, is beneficial to improving the polishing effect and reducing the risk of scratches. However, the existing preparation process is not ideal in controlling the surface morphology of particles. (4) The preparation cost of CeO2 is relatively high, especially in large-scale applications in the semiconductor industry, which increases the cost of the CMP process.

[0006] Therefore, improvements need to be made to the CeO2 used in the CMP process in terms of products and preparation processes to meet the requirements of new preparation technologies for semiconductor surface flatness and to improve the overall performance and efficiency of the CMP process. Summary of the invention

[0007] In order to improve the product performance of CeO2 nanoparticles in the prior art to meet the requirements of CMP process, the present invention proposes a method for preparing nano solid cerium dioxide with bowl-shaped morphology by solvothermal method. The prepared CeO2 nanoparticles have rich oxygen vacancies and high content of Ce in their crystal structure. 3+ , so that the CeO2 particles used as abrasives have high activity and catalytic ability; have low symmetry and a large open bowl-shaped structure, which can improve the polishing effect and reduce the wear and agglomeration of particles during use; and have the advantages of uniform size and large specific surface area, thereby stabilizing the polishing rate. The preparation method is simple in steps, has low requirements for equipment, low raw material prices, does not require the addition of any surfactant, has good repeatability, and can reduce the cost of the CMP process.

[0008] In order to achieve the above object, the first aspect of the present invention provides a method for preparing nano solid cerium dioxide having a bowl-shaped morphology, the method comprising the following steps:

[0009] (1) dissolving Ce(NO3)3·6H2O in ethylene glycol and stirring to form a cerium salt solution;

[0010] (2) adding deionized water under continuous stirring to form a uniform solution;

[0011] (3) transferring the homogeneous solution into an autoclave and carrying out a homogeneous reaction at 175° C. to 185° C. for 15 h to 17 h; and

[0012] (4) The reaction product is cooled to room temperature in air and then carbon thermally reduced to obtain nano-solid cerium dioxide with a bowl-shaped morphology.

[0013] Furthermore, in step (1), the dosage ratio of Ce(NO3)3·6H2O to ethylene glycol is 1 mmol:60 ml.

[0014] Furthermore, in step (1), a cerium salt solution is formed by magnetic stirring for 30 minutes.

[0015] Furthermore, in step (2), the volume ratio of the added deionized water to the ethylene glycol in the cerium salt solution is (2-5):60.

[0016] In a preferred embodiment, in step (2), the volume ratio of deionized water to ethylene glycol is (2-4):60.

[0017] Furthermore, in step (3), the autoclave has a polytetrafluoroethylene lining.

[0018] In a preferred embodiment, in step (3), a homogeneous reaction is carried out at 180° C. for 16 hours.

[0019] Furthermore, in step (4), the conditions for carbon thermal reduction include: placing the reaction product in a muffle furnace after centrifugation, washing, and drying, maintaining the heating rate at 2°C / min, and keeping the temperature at 550°C for 2h in an air atmosphere.

[0020] The present invention also provides nano solid cerium dioxide prepared by any of the above preparation methods, wherein the nano solid cerium dioxide has a bowl-shaped morphology, a particle size of 60-140nm, and a specific surface area of ​​148m 2 g -1 above.

[0021] Furthermore, the opening size of the bowl-shaped morphology is 15-35 nm.

[0022] The beneficial effects of the present invention include:

[0023] 1. The nano solid cerium dioxide obtained by the preparation method of the present invention has uniform size and large specific surface area, and the prepared polishing liquid has a stable polishing rate.

[0024] 2. The nano solid cerium dioxide has a low symmetry and a large-opening bowl-shaped structure, which can improve the polishing effect and reduce the wear and agglomeration of particles during use.

[0025] 3. The nano solid cerium dioxide has a high Ce 3+ content and more oxygen vacancies, and has higher activity and catalytic ability.

[0026] 4. The preparation method has simple steps, low requirements on equipment, low raw material prices, no need to add any surfactant, good repeatability, and can reduce the cost of CMP process. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The X-ray diffraction (XRD) pattern of the product obtained in Example 1 of the present invention.

[0028] Figure 2 This is a scanning electron microscope (SEM) morphology picture of the product obtained in Example 1 of the present invention.

[0029] Figure 3 This is a transmission electron microscope (TEM) morphology picture of the product obtained in Example 1 of the present invention.

[0030] Figure 4 This is the BET diagram of the product obtained in Example 1 of the present invention.

[0031] Figure 5 This is the particle size distribution diagram of the product obtained in Example 1 of the present invention.

[0032] Figure 6 This is a defect size distribution diagram of the product obtained in Example 1 of the present invention.

[0033] Figure 7 This is the X-ray photoelectron spectroscopy (XPS) spectrum of the product obtained in Example 1 of the present invention.

[0034] Figure 8 This is a scanning electron microscope (SEM) morphology picture of the product obtained in Comparative Example 3.

[0035] Fig. 9 This is a transmission electron microscope (TEM) morphology picture of the product obtained in Comparative Example 3.

[0036] Fig.10 This is the BET diagram of the product obtained in Comparative Example 3.

[0037] Fig.11 This is the particle size distribution diagram of the product obtained in Comparative Example 3. DETAILED DESCRIPTION

[0038] In order to better understand the above technical solution, exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings.

[0039] Although the exemplary embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a clearer and more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.

[0040] Example 1

[0041] Dissolve 1mmol Ce(NO3)3·6H2O in 60ml ethylene glycol and stir magnetically for 30min to form a uniform cerium salt solution. Add 2ml deionized water under continuous stirring to form a uniform solution, and then transfer the above solution into an autoclave lined with polytetrafluoroethylene for homogeneous reaction at 180℃ for 16h. After the reaction is completed, the reaction product is cooled to room temperature in air, centrifuged, washed, dried, and placed in a muffle furnace for carbon thermal reduction. The heating rate is maintained at 2℃ / min and kept at 550℃ for 2h in an air atmosphere to obtain nano solid cerium dioxide.

[0042] From the X-ray diffraction (XRD) results ( Figure 1 ), the characteristic diffraction peaks of the sample prepared in Example 1 are all cerium dioxide crystal phase. Scanning electron microscope (SEM) morphology picture ( Figure 2 ) and transmission electron microscopy (TEM) morphology images ( Figure 3 ) shows that the solid cerium dioxide particles prepared in Example 1 have uniform particle size and a smooth surface, and basically have a bowl-shaped opening morphology defect, and the opening edge is a smooth curve.

[0043] The nitrogen adsorption-desorption isotherms of the obtained samples showed a representative type IV isotherm, indicating the porosity of the samples with a specific surface area of ​​149.0118 m 2 g -1 ( Figure 4 ), the particle size distribution is mostly around 130nm±5nm (accounting for more than 2 / 3), and the particle size distribution is narrow ( Figure 5 ); moreover, the bowl-shaped opening size is mostly distributed in the range of 15-35nm, the bowl-shaped defect opening is larger and the size distribution is narrower ( Figure 6 ).

[0044] In addition, the trivalent cerium (Ce 3+ ) content is 17.54% ( Figure 7 ). A larger trivalent cerium content means that there are more oxygen vacancies in the ceria lattice, which can bring greater activity to the ceria nanoparticles.

[0045] Example 2

[0046] Dissolve 1mmol Ce(NO3)3·6H2O in 60ml ethylene glycol and stir magnetically for 30min to form a uniform cerium salt solution. Add 3ml deionized water under continuous stirring to form a uniform solution, and then transfer the above solution into an autoclave lined with polytetrafluoroethylene for homogeneous reaction at 180℃ for 16h. After the reaction is completed, the reaction product is cooled to room temperature in air, centrifuged, washed, dried, and placed in a muffle furnace for carbon thermal reduction. The heating rate is maintained at 2℃ / min and kept at 550℃ for 2h in an air atmosphere to obtain nano solid cerium dioxide.

[0047] The obtained cerium dioxide particles are mostly distributed in the range of 65±5 nm, with uniform particle sizes and smooth surfaces, and basically have a bowl-shaped opening morphology.

[0048] Example 3

[0049] Dissolve 1mmol Ce(NO3)3·6H2O in 60ml ethylene glycol and stir magnetically for 30min to form a uniform cerium salt solution. Add 4ml deionized water under continuous stirring to form a uniform solution, and then transfer the above solution into an autoclave lined with polytetrafluoroethylene for homogeneous reaction at 180℃ for 16h. After the reaction is completed, the reaction product is cooled to room temperature in air, centrifuged, washed, dried, and placed in a muffle furnace for carbon thermal reduction. The heating rate is maintained at 2℃ / min and kept at 550℃ for 2h in an air atmosphere to obtain nano solid cerium dioxide.

[0050] The obtained cerium dioxide particles are mostly distributed in the range of 70±5 nm, with uniform particle sizes and smooth surfaces, and basically have a bowl-shaped opening morphology.

[0051] Example 4

[0052] Dissolve 1mmol Ce(NO3)3·6H2O in 60ml ethylene glycol and stir magnetically for 30min to form a uniform cerium salt solution. Add 5ml deionized water under continuous stirring to form a uniform solution, and then transfer the above solution into an autoclave lined with polytetrafluoroethylene for homogeneous reaction at 180℃ for 16h. After the reaction is completed, the reaction product is cooled to room temperature in air, centrifuged, washed, dried, and placed in a muffle furnace for carbon thermal reduction. The heating rate is maintained at 2℃ / min and kept at 550℃ for 2h in an air atmosphere to obtain nano solid cerium dioxide.

[0053] The obtained cerium dioxide particles are mostly distributed in the range of 105±5nm, with uniform particle sizes and smooth surfaces, and basically have a bowl-shaped opening morphology.

[0054] Comparative Example 1

[0055] Dissolve 1mmol Ce(NO3)3·6H2O in 60ml ethylene glycol and stir magnetically for 30min to form a uniform cerium salt solution. Add 0.5ml deionized water under continuous stirring to form a uniform solution, and then transfer the above solution into an autoclave lined with polytetrafluoroethylene for homogeneous reaction at 180℃ for 16h. After the reaction is completed, the reaction product is cooled to room temperature in air, centrifuged, washed, dried, and placed in a muffle furnace for carbon thermal reduction. The heating rate is maintained at 2℃ / min and calcined at 550℃ for 2h in air atmosphere to obtain nano solid cerium dioxide.

[0056] The obtained cerium dioxide particle size range is 43.5±20.5nm, and the particle size is uneven. It is speculated that the reactants are not completely reacted in this process, and most of them are still in the nucleation process, and only a very small amount of products have a bowl-shaped morphology.

[0057] Comparative Example 2

[0058] Dissolve 1mmol Ce(NO3)3·6H2O in 60ml ethylene glycol and stir magnetically for 30min to form a uniform cerium salt solution. Add 1ml deionized water under continuous stirring to form a uniform solution, and then transfer the above solution into an autoclave lined with polytetrafluoroethylene for homogeneous reaction at 180℃ for 16h. After the reaction is completed, the reaction product is cooled to room temperature in air, centrifuged, washed, dried, and placed in a muffle furnace for carbon thermal reduction. The heating rate is maintained at 2℃ / min and kept at 550℃ for 2h in an air atmosphere to obtain nano solid cerium dioxide.

[0059] The obtained cerium dioxide particle size range is 61.5±20.5nm, and the particle size is uneven. It is speculated that the reactants are not completely reacted in this process, and most of them are still in the nucleation process, and a small amount of products have a bowl-shaped morphology.

[0060] Comparative Example 3

[0061] Dissolve 1mmol Ce(NO3)3·6H2O in 60ml ethylene glycol and stir magnetically for 30min to form a uniform cerium salt solution. Add 6ml deionized water under continuous stirring to form a uniform solution, and then transfer the above solution into an autoclave lined with polytetrafluoroethylene for homogeneous reaction at 180℃ for 16h. After the reaction is completed, the reaction product is cooled to room temperature in air, centrifuged, washed, dried, and placed in a muffle furnace for carbon thermal reduction. The heating rate is maintained at 2℃ / min and kept at 550℃ for 2h in an air atmosphere to obtain nano solid cerium dioxide.

[0062] The particle size of the obtained cerium dioxide is in the range of 110±20.5nm, and the particle size is uneven ( Fig.11); and the specific surface area of ​​the obtained sample is 84.7038m 2 g -1 ( Fig.10 ).

[0063] In addition, scanning electron microscope (SEM) morphology images ( Figure 8 ) and transmission electron microscopy (TEM) morphology images ( Fig. 9 ) shows that the solid cerium dioxide prepared in Comparative Example 3 does not have a bowl-shaped opening morphology, has an uneven surface, has tiny crystal protrusions, and is prone to agglomeration.

[0064] The method of the present invention adopts a solvent thermal method to adjust the particle size and morphological defects of cerium dioxide by changing the amount of deionized water (DI) in the system. When 2-5 ml of deionized water is added, the formed nanoparticles have a more obvious and complete bowl-shaped opening morphology, a smooth surface, and the corresponding particle size and specific surface area are relatively ideal, which can better meet the requirements of the CMP process. When 6-20 ml of deionized water is added, after testing, the resulting particles have no bowl-shaped morphology. When 0.5-1 ml of deionized water is added, although bowl-shaped morphology particles are produced, the number is too small and the particle size is uneven, which is difficult to meet the requirements of the CMP process.

[0065] The reason why different morphologies are caused by different amounts of deionized water added when 2-5 ml of deionized water is added to the system in the method of the present invention is presumably due to the combined effect of the Ostwald ripening mechanism and the induction of internal stress. Deionized water simultaneously regulates the growth rate of each crystal face of the cerium oxide nanocrystal, and the anisotropic growth of the cerium oxide crystal eventually leads to the appearance of a bowl-shaped opening morphology.

[0066] The present invention proposes a nano solid cerium dioxide with a large opening bowl-shaped morphology and a preparation method thereof, specifically using a solvothermal method to prepare a bowl-shaped solid cerium dioxide nano powder with a high specific surface area and uniform particle size, which can meet the requirements of the new preparation technology for the surface flatness of semiconductors and improve the overall performance and efficiency of the CMP process. The preparation method of the present invention is simple and has low requirements for equipment; the raw materials are inexpensive, no surfactant needs to be added, the repeatability is good, and the cost of the CMP process can be reduced.

[0067] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may alter, modify, replace and modify the above embodiments within the scope of the present invention.

Claims

1. A method for preparing nano solid cerium dioxide with a bowl-shaped morphology, characterized in that: The method comprises the following steps: (1) dissolving Ce(NO3)3·6H2O in ethylene glycol and stirring to form a cerium salt solution; (2) adding deionized water under continuous stirring to form a uniform solution; (3) transferring the homogeneous solution into an autoclave and carrying out a homogeneous reaction at 175° C. to 185° C. for 15 h to 17 h; and (4) The reaction product is cooled to room temperature in air and then carbon thermally reduced to obtain nano-solid cerium dioxide with a bowl-shaped morphology.

2. The method according to claim 1, characterized in that In step (1), the dosage ratio of Ce(NO3)3·6H2O to ethylene glycol is 1 mmol:60 ml.

3. The method according to claim 1, characterized in that In step (1), a cerium salt solution is formed by magnetic stirring for 30 minutes.

4. The method according to claim 1, characterized in that: In step (2), the volume ratio of the added deionized water to the ethylene glycol in the cerium salt solution is (2-5):

60.

5. The method according to claim 4, characterized in that In step (2), the volume ratio of deionized water to ethylene glycol is (2-4):

60.

6. The method according to claim 1, characterized in that In step (3), the autoclave has a polytetrafluoroethylene lining.

7. The method according to claim 1, characterized in that In step (3), a homogeneous reaction is carried out at 180°C for 16 hours.

8. The method according to claim 1, characterized in that In step (4), the conditions for carbon thermal reduction include: placing the reaction product in a muffle furnace after centrifugation, washing, and drying, maintaining the heating rate at 2°C / min, and keeping the temperature at 550°C for 2h in an air atmosphere.

9. The nano solid cerium dioxide prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The nano solid cerium dioxide has a bowl-shaped morphology, a particle size of 60-140nm, and a specific surface area of ​​148m 2 g -1 above.

10. The nano solid cerium dioxide according to claim 9, characterized in that: The opening size of the bowl-shaped morphology is 15-35 nm.